2019
DOI: 10.1200/jco.18.01567
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Therapeutics for Chronic Cancer Pain: A Bayesian Network Meta-Analysis

Abstract: PURPOSE Opioids are the primary choice for managing chronic cancer pain. However, many nonopioid therapies are currently prescribed for chronic cancer pain with little published evidence comparing their efficacy. METHODS Electronic databases were searched for randomized controlled trials (RCTs) comparing any systemic pharmaceutical intervention and/or combination thereof in treating chronic cancer pain. The primary outcome was global efficacy reported as an odds ratio (OR). The secondary outcome was change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
0
27
0
1
Order By: Relevance
“…Therefore, the European Society of Medical Oncology stated that there is no reason to recommend or refute paracetamol for mild-to-moderate cancer pain [ 125 ]. Conversely, a 2019 network meta-analysis of analgesic drugs for chronic cancer pain concluded that the top-ranking drug classes for global efficacy were non-opioid analgesics, including paracetamol, as well as NSAIDs and opioids [ 126 ]. It is considered the first-choice drug for mild-to-moderate pain in older patients with cancer naïve to opioids [ 127 ].…”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…Therefore, the European Society of Medical Oncology stated that there is no reason to recommend or refute paracetamol for mild-to-moderate cancer pain [ 125 ]. Conversely, a 2019 network meta-analysis of analgesic drugs for chronic cancer pain concluded that the top-ranking drug classes for global efficacy were non-opioid analgesics, including paracetamol, as well as NSAIDs and opioids [ 126 ]. It is considered the first-choice drug for mild-to-moderate pain in older patients with cancer naïve to opioids [ 127 ].…”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…In a world in which reviews of previous reviews are increasingly published, looking for misleading evidence and leading scientists to rise up against statistical significance [5], a pragmatic approach may better select data reflecting the clinical reality, instead of indicating unlikely clinical evidence [6]. I was dismayed and shocked when reading the results of a recent review [7], in part because it was published in an authoritative journal. It is suggested that non-opioid analgesics and NSAIDs can be effective as opioid therapy, in contrast to the presumed superiority of opioids.…”
mentioning
confidence: 99%
“…Of these 50 potentially relevant articles, 33 publications were excluded for various reasons and 17 publications met the inclusion criteria and were included in this report. These comprised 3 overviews of reviews 28-30 (i.e., systematic reviews of systematic reviews) and 13 systematic reviews [31][32][33][34][35][36][37][38][39][40][41][42][43][44] (5 with meta-analysis [31][32][33]37,42,44 and1 with network-meta analysis), 38 1 of which was reported in 2 publications. 32,33 Appendix 1 presents the PRISMA 45 flow chart of the study selection.…”
Section: Quantity Of Research Availablementioning
confidence: 99%